Determinants of Women’s Choice of a Long-Acting Reversible Contraceptive in Boyolali, Central Java - Desy Eka Ilmiyah; Uki Retno Budihastuti; Ismi Dwi Astuti Nurhaeni; Ambar Mudigdo (Journal of Maternal and Child Health, 2018)
Background: Long-acting reversible contraceptives (LARCs) are the most effective methods of birth control. LARCs include the copper IUD, the hormonal (progesterone) IUD, and the hormonal contraceptive implant (effective for 10, 5 and 3 years, respectively). These methods of birth control can prevent unwanted pregnancy up to 20 times better than birth control pills, patches, and vaginal rings. However, the use of LARCs remains low in Boyolali, Central Java, Indonesia. This study aimed to analyze the determinants of women’s choice of a LARC in Boyolali, Central Java. Subjects and Method: This was a case control study conducted in 25 community health centers, Boyolali District, Central Java, from April 24 to May 20, 2018. A sample of 200 women in reproductive age was selected by fixed disease sampling. The dependent variable was choice of a LARC. The independent variables were age, education, parity, knowledge, husband support, and counseling by health worker. The data were collected by questionnaire and analyzed by a logistic regression multilevel using Stata 13 program. Results: Women’s choice of the LARC increased with age ≥35 years (b= 4.54; 95% CI= 1.69 to 12.15; p= 0.003), education ≥senior high school (b= 4.59; 95%CI= 1.80 to 11.70; p= 0.001), parity ≥3 (b = 7.15; 95%CI= 2.63 to 19.44; p<0.001), better knowledge (b= 2.20; 95% CI= 0.88 to 5.50; p= 0.089), counseling by health worker (b= 2.82; 95% CI= 1.11 to 7.11; p= 0.028), and husband support (b= 5.54; 95% CI= 2.15 to 14.28; p<0.001). Conclusion: Women’s choice of LARC increases with age ≥35 years, education ≥senior highschool, parity ≥3, better knowledge, counseling by health worker, and husband support.